Revision of interface coupling in ultra-thin body silicon-on-insulator MOSFETs - Rudenko, T.; Nazarov, A.; Kilchytska, V.; Flandre, D.; Popov, V.; Ilnitsky, M.; Lysenko, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The charge coupling between the gate and substrate is a fundamental property
of any fully-depleted silicon-on-insulator (SOI) MOS transistor, which manifests itself as
a dependence of electrical characteristics at one Si film/dielectric interface on charges at
the opposite interface and opposite gate bias. Traditionally, gate-to-substrate coupling in
SOI MOS transistors is described by the classical Lim-Fossum model. However, in the
case of SOI MOS transistors with ultra-thin silicon bodies, significant deviations from
this model are observed. In this paper, the behavior of gate coupling in SOI MOS
structures with ultra-thin silicon films and ultra-thin gate dielectrics is studied and
analyzed using experimental data and one-dimensional numerical simulations in classical
and quantum-mechanical modes. It is shown that in these advanced transistor structures,
coupling characteristics (dependences of the front- and back-gate threshold voltages on
the opposite gate bias) feature a larger slope and much wider (more than doubled) linear
region than that predicted by the Lim-Fossum model. These differences originate from
both electrostatic and quantization effects. A simple analytical model taking into account
these effects and being in good agreement with numerical simulations and experimental
results is proposed.